(untitled) (Singapore, 2001)
This is an invaluable collection of colloquium-type lectures given by some of the most prominent theoretical physicists of today. In a form accessible to the interested general physicist, it covers topics ranging from the use of field-theoretical methods in different contexts via duality symmetries between various field theories, to the Ads/CFT correspondence and cosmology.
Keywords: Physics,Quantum theory,Vật lý,Lý thuyết lượng tử